KONFLIK KERJA KELUARGA DAN WELAS DIRI TERHADAP RESILIENSI - Azkiya, Nisrina; Prestiana, Novita Dian Iva; Setiawan, Rony (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Teachers in primary schools play an important role in the early education of their students. Research in one region of Indonesia revealed that 73% of teachers experienced high job stress, so a teacher must have resilience. The purpose of this study was to determine the effect of work-family conflict and self- compassion on resilience in teachers. This study used a quantitative approach, involving 74 female teachers from 5 SDN Sindangmulya Cibarusah. The data collection methods in this study were interviews and psychological scales. The research instruments used were The Connor-Davidson Resilience Scale Self (CD-RISC), Work Family Conflict Scale, and Self Compassion Scale. Instrument reliability test using Cronbach Alpha. Data analysis used Pearson product moment correlation test and simple linear regression. The correlation test results show a value of r = -0.558, p = 0.000 which means there is a moderate and significant negative relationship between family work conflict and resilience. Then the correlation test value of r = 0.787, p = 0.000 which means that there is a strong and significant positive relationship between self-compassion and resilience